The disaster of Numantia and the numismatic iconography: rereading two denarii minted in 137 BCE (Romanitas - Revista de Estudos Grecolatinos, 2018)
The purpose of this article is to analyze the monetary images of two denarii minted in Rome in the year 137 BCE in order to reflect on the relation of these coinage with the debate that occupied a large part of the Roman elite that year, regarding ratification or not of the treaty made by the general Caius Hostilius Mancinus with the city of Numantia. The pieces were issued by the monetaries Tiberius Veturius and Sextus Pompeius. Representations of deities and references to the ancestors and the past of the city of Rome participate in the elaboration of the numismatic discourse, revealing opposing positions on the ongoing debate.
Keywords: Roman Republic; Monetary images; Treaty of Numantia; Gods; Ancestors